2018
DOI: 10.1038/s41598-018-33344-8
|View full text |Cite
|
Sign up to set email alerts
|

Tender leaf and fully-expanded leaf exhibited distinct cuticle structure and wax lipid composition in Camellia sinensis cv Fuyun 6

Abstract: The goal of the present study was to compare the structural and compositional differences of cuticle between tender leaf and fully-expanded leaf in Camellia sinensis, and provide metabolic base for the further characterization of wax biosynthesis in this economically important crop species. The tender second leaf and the fully-expanded fifth leaf from new twig were demonstrated to represent two different developmental stages, their cuticle thickness were measured by transmission electron microscopy. The thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 46 publications
3
48
0
Order By: Relevance
“…In total, 354-393 compounds were detected from the wax mixtures of CK samples (n = 3) and 397-414 compounds were detected from those of LD samples (n = 3) (Supplemental Table S12). The wax mixtures on sampled tea leaves from both groups consisted mainly of fatty acids, alkanes, alkenes, aldehydes, and primary alcohols, similar to a recent report on the predominant wax constituents of tender tea leaves (Zhu et al, 2018) ( Table 3).…”
Section: Tea Green Leafhopper-infested Tea Leaves Show Higher Accumulsupporting
confidence: 86%
See 3 more Smart Citations
“…In total, 354-393 compounds were detected from the wax mixtures of CK samples (n = 3) and 397-414 compounds were detected from those of LD samples (n = 3) (Supplemental Table S12). The wax mixtures on sampled tea leaves from both groups consisted mainly of fatty acids, alkanes, alkenes, aldehydes, and primary alcohols, similar to a recent report on the predominant wax constituents of tender tea leaves (Zhu et al, 2018) ( Table 3).…”
Section: Tea Green Leafhopper-infested Tea Leaves Show Higher Accumulsupporting
confidence: 86%
“…To compare the differences in leaf wax compositions between CK and LD groups, total cuticular wax was extracted and analyzed as previously described (Zhu et al, 2018). Tea leaves were soaked with 5 ml of chloroform containing 10 µg of n-tetracosane (internal standard) for 30 s at room temperature.…”
Section: Leaf Cuticular Wax Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…After bud break new leaves are sequentially emerged, thus form a developmental gradient along the new branch: the leaves next to the apical bud are newly developed and are more tender; in contrast, the leaves located at the lower part of the branch are emerged earlier thus more mature. Along this developmental gradient, Zhu et al 3 demonstrated that leaf cuticular wax experienced dramatic compositional changes with leaf maturation: alicyclic compounds did not present from the tender second leaf but dominate the mature fifth leaf. Thus, in this study only the second leaf and the fifth leaf were selected to represent the tender leaf and mature leaf, respectively.…”
mentioning
confidence: 99%